2006
DOI: 10.3758/bf03193389
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent task effects on memory encoding and retrieval: Further support for an asymmetry

Abstract: Several studies have demonstrated that divided attention at encoding significantly reduces memory performance, whereas divided attention at retrieval affects memory performance only minimally. However, the possibility exists that retrieval processes have shown such resilience because the concurrent tasks used have often not been very demanding. To assess this possibility, we used independent manipulations of the concurrent task during either encoding or retrieval that included stimulus-response compatibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 22 publications
(57 reference statements)
4
45
1
Order By: Relevance
“…Second, and most importantly, there is considerable evidence to suggest that there is an asymmetric pattern of interference between retrieval and secondary task demands in dual-task settings. Specifically, retrieval efficacy is rarely affected by the concurrent performance of a continuously demanding secondary task, but retrieval may significantly impair that secondary task's performance (Craik, Govoni, Naveh-Benjamin, & Anderson, 1996; Kellogg, Cocklin, & Bourne, 1982; Naveh-Benjamin, Craik, Perretta, & Tonev, 2000; Naveh-Benjamin, Kilb, & Fisher, 2006). Thus, retrieval from WM appears to be an obligatory, protected process that is unimpaired by concurrent task demands (Craik et al, 1996; Naveh-Benjamin, Craik, Guez, & Dori, 1998; Naveh-Benjamin et al, 2000, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Second, and most importantly, there is considerable evidence to suggest that there is an asymmetric pattern of interference between retrieval and secondary task demands in dual-task settings. Specifically, retrieval efficacy is rarely affected by the concurrent performance of a continuously demanding secondary task, but retrieval may significantly impair that secondary task's performance (Craik, Govoni, Naveh-Benjamin, & Anderson, 1996; Kellogg, Cocklin, & Bourne, 1982; Naveh-Benjamin, Craik, Perretta, & Tonev, 2000; Naveh-Benjamin, Kilb, & Fisher, 2006). Thus, retrieval from WM appears to be an obligatory, protected process that is unimpaired by concurrent task demands (Craik et al, 1996; Naveh-Benjamin, Craik, Guez, & Dori, 1998; Naveh-Benjamin et al, 2000, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Although possible, it should be noted that: (a) the same secondary task which had a small interference eVect on retrieval of NNAs, had a large eVect on their encoding in Experiment 1, and, (b) increases in the diYculty of memory retrieval in Experiment 2 decreased secondary task performance, not memory for NNAs (for further discussion, see Naveh-Benjamin, Kilb, & Fisher, 2006). An alternative possibility is that participants focused on the secondary lag 1 task when attention was divided at encoding, but focused on the NNA task when attention was divided at retrieval.…”
Section: Discussionmentioning
confidence: 98%
“…Some previous DA studies have reported that the DA task disrupts memory performance minimally when it is administrated at retrieval compared to when it is performed during the encoding of information (e.g., Baddeley, Lewis, Eldridge, & Thomson, 1984;Craik, Govoni, Naveh-Benjamin, & Anderson, 1996;Naveh-Benjamin, Craik, Guez, & Dori, 1998;Naveh-Benjamin, Kilb, & Fisher, 2006). In addition, Park, Smith, Dudley, and Lafronza (1989) reported that the effect of DA was very small during retrieval and that the effect was similar for young and older adults.…”
Section: Future Directionsmentioning
confidence: 92%